Silver nanofiber membranes for indoor air pollution treatment - K.V. Radha; V.S. Selvi; J. Aarcha (Sustainable Chemistry for Climate Action)
Fresh air is essential for a healthy life but is being polluted due to day-to-day changes in lifestyle. Air purification systems using nanotechnology has started to come into existence providing effective solution at low cost and less energy. The review on investigating the antibacterial and antifungal activity of the synthesised Ag nanoparticles revealed significant amount of antimicrobial activity against airborne pathogens such as Bacillus subtilis, Bacillus megaterium, Staphylococcus aureus, Pseudomonas aeruginosa, Pseudomonas putida, Escherichia coli, Aspergillus niger, Aspergillus ficuum, Rhizopus stolonifer and Phanerochaete chrysosporium were observed. Nanoparticles incorporated membrane is expected to target the contaminants present in the air and treat it effectively. Air filtration studies on the performances of the nanofiber membranes against bacterial and fungal aerosol showed the filtration efficiency and antimicrobial efficiency increased with the Ag nanoparticles amount, and that it decreased with the amount of microbial loading. The actual and theoretical antimicrobial efficiency tests yielded the maximum antibacterial and antifungal efficacy at 98.33 % and 99.86 %, respectively. All these factors prove that the emergence of silver nanofiber membranes as an antimicrobial agent is a promising future for the treatment of air pollution.